Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Solve.- 6x^2 + 6 - 2x = xChoose 1 answer:

Solve 6x2 6 2x XChoose 1 Answer class=

Sagot :

Solve.

- 6x^2 + 6 - 2x = x

6 x^2 + 2x + x - 6 =0

6 x ^2 + 3 x - 6 = 0

Divide through by 6,

x ^2 + 1/2x - 1 = 0

a = 1, b = 1/2, c = -1

Solving using Quadratic formula,

Option D is correct

We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.